MEASURING THE CORRELATION COGNITIVE DISSONANCE BIAS, HIND SIGHT BIAS, OVER CONFIDENCE BIAS AND SELF-CONTROL BIAS TO INVESTMENT DECISION ON STOCK OPTION - Dody Suhermawan; Almira Vidhayandika M (Journal of Managerial Sciences and Studies, 2024)
Researchers want to know the effects of cognitive dissonance bias, hindsight bias, overconfidence bias, and self-control bias on Stock Option investment decisions. The researcher uses the technical analysis of convergent validity test, discriminant validity test, outer model test, inner model test, rsquare, hypothesis test and Sobel test. The program used is SmartPLS 3 trial version with a sample of 224 respondents with predetermined criteria. The results show that the cognitive dissonance bias variable on Stock Option investment decisions has no significant effect, the hindsight bias variable has no effect on Stock Option investment decisions, overconfidence bias has a positive but not significant effect on Stock Option investment decisions. This is because the T-statistic value is less than 1.97. While the self-control variable can have a positive and significant effect on Stock Option investment decisions.